"When you give birth you will not be without your mother" A mixed methods study of advice on breastfeeding for first-time mothers in rural coastal Kenya. Issue 1 (December 2016) - Talbert, Alison; Ngari, Moses; Tsofa, Benjamin; Mramba, Lazarus; Mumbo, Edward; Berkley, James; Mwangome, Martha
Abstract Background Exclusive breastfeeding for the first 6 months of life is currently recommended by the World Health Organization, but mixed feeding earlier than this commonly occurs in rural coastal Kenya. Mothers may receive conflicting advice on breastfeeding from various sources including health workers, relatives and community members. We aimed to find out how first-time mothers learn to breastfeed, who advises them on infant feeding and what advice they obtain in case of any breastfeeding problems. Methods To identify advisers, a questionnaire on socio-demographic status, place of delivery, household members, education and help received on breastfeeding, breastfeeding problems, name of advisers and their relationship to the mothers was administered to 50 new first-time mothers in Jaribuni, Kilifi (population approximately 18, 000). Summary statistics were obtained using frequencies, medians and interquartile ranges (IQR). Focus group discussions (FGDs) were held amongst 4 groups of mothers who had answered questionnaires; 4 groups of their named advisers; and 1 group of community health workers in order to explore breastfeeding practices, problems and advice given. FGDs were analysed by thematic framework analysis. Results First-time mothers were young (median age 18, IQR 17–21, range 14–26 years) and 42 % were single. Living in extended families was the norm and married women lived with their husband's family. All had a female family member or neighbour helping with childcare in the perinatal period. The main advisers on breastfeeding were their mother or older female members of their husband's family. Married first-time mothers felt obliged to follow their mother-in-law's advice to maintain good relationships and show respect within the household. Breastfeeding problems were reported by 80 % of respondents. Nipple pain (56 %) was the most reported problem, then breast engorgement (48 %) and insufficient milk supply (38 %). Most problems were treated at home without consultation with health workers. Concerns were raised about co-sleeping, breastfeeding whilst lying down, and insufficient milk supply. Advisers would like more information on breastfeeding in order to help mothers. Conclusions Interventions to increase knowledge of, and facilitate optimal breastfeeding practices in first-time mothers should include those family members who advise and assist with childcare around the time of delivery.